Brown-Séquard syndrome without vascular injury associated with Horner's syndrome after a stab injury to the neck. (January 2016) - Johnson, Stephen; Jones, Margaret; Zumsteg, Jennifer
Abstract : Case Description: This case reviews the acute care and rehabilitation course of a 44-year-old right-handed woman after an assault with a pocketknife. She suffered multiple stab wounds including penetrating injury to the left side of her neck. Physical examination revealed left hemiplegia (motor score = 57), impaired pinprick sensation on the right caudal to the C5 dermatome, impaired joint position sense on the left, and left ptosis and miosis. Initially she was unable to stand without maximum assistance. MR imaging revealed transection of the left hemicord at the C5 level without cord hemorrhage. CTA of the neck was negative for vascular injury. She completed 18 days of acute inpatient rehabilitation. She used forearm crutches for ambulation at time of discharge. Prior to discharge the patient provided written permission for a case report. Discussion: Stab wounds are the most common cause of traumatic Brown-Séquard syndrome. Horner's syndrome is common in spinal cord lesions occurring in the cervical or thoracic region, however the combination of Horner's and Brown-Séquard syndromes is less commonly reported. In this case report, we review recommendations regarding initial imaging following cervical stab wounds, discuss anatomy and associated neurological findings in Brown-Séquard and Horner's syndromes, and review the expected temporal course of motor recovery. Conclusions: Facilitating motor recovery and optimizing function after Brown-Séquard spinal cord injury are important roles for the rehabilitation team. Imaging is necessary to rule out cord hemorrhage or vascular injury and to clinically correlate cord damage with physical examination findings and expected functional impairments. Documenting associated anisocoria and explaining this finding to the patient is an important element of spinal cord injury education. Commonly, patients with Brown-Séquard injuries demonstrate remarkable motor recovery and regain voluntary motor strength and functional ambulation.